Maintaining Teacher Performance and Motivation: Challenges and Strategies for Human Resource Management in the Education Sector - Kadar Nurjaman (STAI Hubbulwathan Duri, 2023)
Teachers need recognition and gratitude for their efforts, as well as guidance and help to improve their performance. The purpose of this study is to analyze the challenges and strategies for human resource management in education to maintain teacher performance and motivation. The research uses a systematic literature review method. The database used in this study is Scopus. Data collection involves 260 publication documents in total. Limitations are made to select better data, in which case only documents form final articles using English. Data was obtained after the limitation of 196 publication documents. Data analysis is performed using NVivo software. Results show that efficient human resource management (SDM) strategies in the process of maintaining educational performance and motivation are essential and difficult to execute effectively. To succeed in overcoming these obstacles, human resource management must adopt strategies that include all of them and demonstrate sensitivity to the specific requirements of each educator. Then educational institutions must be able to develop an atmosphere that encourages, motivates, and maintains high-performing teachers when they execute efficient plans for human resource management (HDM).